2022
DOI: 10.3390/ani12182407
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Black Soldier Fly Frass as an Ingredient in Florida Pompano (Trachinotus carolinus L.) Diets

Abstract: The aquaculture industry is in need of sustainable fish feed to reduce the use of expensive and environmentally invasive wild-caught fish currently fed to many carnivorous species. The black soldier fly (BSF) has become a popular sustainable alternative protein source; however, the nutritional waste byproduct of BSF, frass, has not been extensively studied as a feed replacement in carnivorous species. This study evaluates the potential of BSF frass on the growth, body composition, and intestinal microbiome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Currently, agriculture, horticulture and retail appear as the primary markets for frass applications as a fertilizer (Chavez and Uchanski 2021) , Larouche 2022. However, applications of frass as a potential ingredient in animal feed (fish , Banavar, Amirkolaei et al 2022), shrimp (Yildirim-Aksoy, Eljack et al 2022, rabbits (Radwan, Maggiolino et al 2023)), and/or secondary processing (feedstock for biomethanisation (Wedwitschka, Gallegos Ibanez and Jáquez 2023), for composting (Song, Ee et al 2021), or for biochar production (Yang, Chen et al 2019, Yang, Zhang et al 2019)) are emerging. Considering the strong growth of the edible insect sector, and the high ratio of frass production per tonne of edible insects harvested, it is therefore important to find value-added opportunities to consolidate the economic model of current and future insect productions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, agriculture, horticulture and retail appear as the primary markets for frass applications as a fertilizer (Chavez and Uchanski 2021) , Larouche 2022. However, applications of frass as a potential ingredient in animal feed (fish , Banavar, Amirkolaei et al 2022), shrimp (Yildirim-Aksoy, Eljack et al 2022, rabbits (Radwan, Maggiolino et al 2023)), and/or secondary processing (feedstock for biomethanisation (Wedwitschka, Gallegos Ibanez and Jáquez 2023), for composting (Song, Ee et al 2021), or for biochar production (Yang, Chen et al 2019, Yang, Zhang et al 2019)) are emerging. Considering the strong growth of the edible insect sector, and the high ratio of frass production per tonne of edible insects harvested, it is therefore important to find value-added opportunities to consolidate the economic model of current and future insect productions.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that larval frass from the by-product of black soldier fly larvae (BSFL) has a growth-promoting effect on channel catfish through increasing palatability and feed intake [18]. Besides its promising value as a feed ingredient for several fish species, such as channel catfish (Ictalurus punctatus) [18,19], hybrid tilapia (Oreochromis niloticus × O. mozambique) [20], and Florida Pompano (Trachinotus carolinus L.) [21], frass contains abundant nutrients, chitin-a naturally occurring biopolymer from invertebrate shells-and beneficial microbes [22,23]. In fact, the use of frass in tilapia diets have shown to be beneficial by improving innate immune components and subsequently, the resistance of hybrid tilapia against bacterial infection [20] as well as increasing the serum antibacterial effect of Pacific white shrimp, Litopenaeus vannamei, against Vibrio parahemolyticus [24].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota modulation can also affect lipid metabolism and the balance of energy ( 18 ) . It also seems that certain BSF diets do not improve the microbiota diversity in carnivorous fish in a balanced way but could be more beneficial in herbivore and detritivore fish species ( 19 ) .…”
mentioning
confidence: 99%